E-government effectiveness and efficiency in EU-28 and COVID-19 - Hodžić, Sabina (Central European Public Administration Review, 2021)
The task of every government, especially during the Covid-19 pandemic, is to provide services and goods for citizens and to maintain economic order. Therefore, the combination of legislation, the judiciary and administration is inevitable. Moreover, public administrations must transform the way they function by using more information and communication technology in order to remain responsive and efficient. This challenge was further revealed during lockdowns in individual countries, which affected their social and economic development. The solution to that challenge is the implementation of e-government in the public sector. It also increases innovation in governance processes as well as efficiency and effectiveness by offering more participative opportunities to citizens. Hence, a mature level of e-government development also arises. Nevertheless, there are significant differences among the levels of e-government development in the EU-28. The aim of this article is to assess the influence of e-government maturity on government effectiveness and efficiency in the EU-28. In order to obtain empirical results, a two-stage least square regression (2SLS) was applied. The empirical results show that e-government maturity positively and significantly contributes to enhancing government effectiveness and efficiency in the EU-28. In addition, the rule of law plays an important role in each stage regression model. Based on the empirical results, we can conclude that e-government is inevitable and should ensure the proper functioning of public administration during the Covid-19 pandemic.
Keywords: Covid-19 measures; e-government; e-uprava; government effectiveness; government efficiency; regresijska analiza 2SLS; two-stage least squares regression analysis; učinkovitost upravljanja; ukrepi, povezani s covidom-19; uspešnost upravljanja